Effects of esketamine–sufentanil for patient-controlled intravenous analgesia in women following cesarean section: A randomized clinical trial - Zhao, Yanping; Liu, Lin; Hou, Yi; Fan, Jiaming (Frontiers in Pharmacology, 2025)
BackgroundPostoperative pain following cesarean section can cause maternal anxiety, limited ambulation, and even postpartum depression. In this study, we aimed to investigate the effects of esketamine for postoperative patient-controlled intravenous analgesia in women following cesarean section.MethodsOne hundred women were randomly assigned to two groups. The esketamine group received 1 mg⋅kg-1⋅d-1 of esketamine +1 µg⋅kg-1⋅d-1 of sufentanil for intravenous postoperative analgesia, and the control group received 1 µg⋅kg-1⋅d-1 of sufentanil for intravenous analgesia. The primary outcome was the pain intensity during the postoperative 24 h, and it was assessed using a visual analog scale (VAS). The secondary outcomes included hemodynamic parameters, total consumption of analgesics, blood loss, and drug-related side effects (hypotension, hypertension, bradycardia, nausea, and vomiting).ResultsThe VAS scores at rest were lower in the esketamine group than in the control group during the postoperative 6 h–24 h (p < 0.05), and the VAS scores at cough in the esketamine group were lower during the postoperative 4 h–24 h (p < 0.05). There were significant differences at blood loss during the postoperative 24 h (137.6 ± 33.0 vs 159.6 ± 41.3 mL, p = 0.004). Blood pressure and heart rate were greater in the esketamine group than in the control group during the postoperative 8 h–24 h (p < 0.05). The incidence of nausea and vomiting was significantly lower in the esketamine group than in the control group (4% vs 18%, p = 0.025).ConclusionThis study indicated that esketamine not only improved postoperative pain but also reduced postpartum blood loss and the incidence of nausea and vomiting in women undergoing cesarean section (registration number: ChiCTR2400082094).Systematic Review Registrationhttps://www.chictr.org.cn, Identifier ChiCTR2400082094